Toward panoramic in situ mapping of action potential propagation in transgenic hearts to investigate initiation and therapeutic control of arrhythmias - Dura, Miroslav; Schröder-Schetelig, Johannes; Luther, Stefan; Lehnart, Stephan E. (Frontiers in Physiology, 2014)
To investigate the dynamics and propensity for arrhythmias in intact transgenic hearts comprehensively, optical strategies for panoramic fluorescence imaging of action potential (AP) propagation are essential. In particular, mechanism-oriented molecular studies usually depend on transgenic mouse hearts of only a few millimeters in size. Furthermore, the temporal scales of the mouse heart remain a challenge for panoramic fluorescence imaging with heart rates ranging from 200 min-1 (e.g. depressed sinus node function) to over 1200 min-1 during fast arrhythmias. To meet these challenging demands, we and others developed physiologically relevant mouse models and characterized their hearts with planar AP mapping. Here, we summarize the progress towards panoramic fluorescence imaging and its prospects for the mouse heart. In general, several high-resolution cameras are synchronized and geometrically arranged for panoramic voltage mapping and the surface and blood vessel anatomy documented through image segmentation and 3D heart surface reconstruction. We expect that panoramic voltage imaging will lead to novel insights about molecular arrhythmia mechanisms through quantitative strategies and 3D analysis of intact mouse hearts.